2013
DOI: 10.3391/ai.2013.8.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Globalization pressure and habitat change: Pacific rocky shore crabs invade armored shorelines in the Atlantic Wadden Sea

Abstract: Florence, was a brilliant Italian zoologist and ethologist, and one of the most well-known and active experts on alien aquatic species. Since her masters degree in Biology (1979) and her PhD in Animal Biology (Ethology) (1987), both obtained at the University of Florence, Francesca studied the behaviour and ecology of aquatic animals. Initially, most of her research concerned social recognition in crustaceans: she was particularly renowned for her studies on hermit crabs and crayfish, her principal model orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…In addition, predation effects of different cercarial predators may also be additive when they cooccur, resulting in further reductions of infection levels (Thieltges et al 2009). With all three cercarial predators co-occurring locally in the Wadden Sea (Troost 2010, Witte et al 2010, Landschoff et al 2013, the actual total cercarial consumption will thus depend on the species composition around target mussels. Interestingly, the mussels themselves will also act as sentinels, i.e., increasing mussel densities will lead to reduced infection levels per individual host (Thieltges et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, predation effects of different cercarial predators may also be additive when they cooccur, resulting in further reductions of infection levels (Thieltges et al 2009). With all three cercarial predators co-occurring locally in the Wadden Sea (Troost 2010, Witte et al 2010, Landschoff et al 2013, the actual total cercarial consumption will thus depend on the species composition around target mussels. Interestingly, the mussels themselves will also act as sentinels, i.e., increasing mussel densities will lead to reduced infection levels per individual host (Thieltges et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the northern Wadden Sea, the Asian shore crab has survived three consecutive winters (2010 -2012) during which ice covered the shore and water temperatures dropped to 228C (Landschoff et al, 2013). According to Gittenberger et al (2010), Hemigrapsus sanguineus is also only found at locations with a salinity of ≥19.…”
Section: Discussionmentioning
confidence: 99%
“…The breeding season lasts from May to September and a female can produce 2-4 batches of eggs, 50,000 eggs per spawning (Fukui, 1988;McDermott, 1998a). However, Landschoff et al (2013) reported that on the ice-covered shores of the northern Wadden Sea, with water temperatures at 228C, H. sanguineus aggregated, slowly crawling, even with ovigerous females, under boulders at low-tide level. This suggests that the Asian shore crab can be ovigerous all year round in north-east Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include competition for resources, e.g. Hemigrapsus sanguineus (de Haan, 1853) being able to displace juvenile Carcinus maenas (Linnaeus, 1758) from shelter (Landschoff et al, 2013) and as vectors for disease, e.g. Pacifastacus leniusculus (Dana, 1852) a known carrier of crayfish plague which has caused rapid decline in populations of Austropotamobius pallipes (Lereboullet, 1858) within the UK (Lilley et al, 1997).…”
Section: Introductionmentioning
confidence: 99%